On Apologizing in Norwegian - Awedyk, Witosław (Katedra Skandynawistyki UAM, 2011)
This paper discusses selected points concerning the verbal realization of the speech act of apology in Norwegian. It sets out to establish prevailing tendencies in the choice of apology strategies applied by the native speakers of Norwegian. The present findings, which seem to indicate that Norwegian apology strategies are fairly routinized, ought to be perceived as preliminary as a more detailed analysis of apology formulae will be presented in an upcoming article.
Keywords: speech acts; apologizing; Norwegian; apologizing in Norwegian